Fatigue and Fracture of Weldments The IBESS Approach for the Determination of the Fatigue Life and Strength of Weldments by Fracture Mechanics Analysis - Zerbst, Uwe; Madia, Mauro; Schork, Benjamin; Hensel, Jonas; Kucharczyk, Pawel; Ngoula, DesireTchoffo; Tchuindjang, Didi; Bernhard, Julian; Beckmann, Carla (Springer International Publishing : Imprint: Springer, 2019)
This book provides a comprehensive and thorough guide to those readers who are lost in the often-confusing context of weld fatigue. It presents straightforward information on the fracture mechanics and material background of weld fatigue, starting with fatigue crack initiation and short cracks, before moving on to long cracks, crack closure, crack growth and threshold, residual stress, stress concentration, the stress intensity factor, J-integral, multiple cracks, weld geometries and defects, microstructural parameters including HAZ, and cyclic stress-strain behavior. The book treats all of these essential and mutually interacting parameters using a unique form of analysis.